Wear Characteristics Of Recycled Carbon Fibre-Filled Polypropylene Composites Via Acidic Surface Treatment - Mohamad, Noraiham; Abd Latiff, Anisah; Abd Manaf, Mohd Edeerozey; Ab Maulod, Hairul Effendy; Shueb, Mohammed Iqbal; Munawar, Rose Farahiyan; Raja Abdullah, Raja Izamshah; Kasim, Mohd Shahir; Mazlan, Mazliah; Abd Razak, Jeefferie; Mohd Abid, Mohd Asyadi Azam (World Association for Sustainable Development, 2018)

(untitled)
Recycling and reuse of waste carbon fibre for making value-added products is a wise disposal management.This research is focusing on the tribological potential of nitric acid treated recycled carbon fibres (rCFs) as reinforcement in polypropylene (PP).The coefficients of friction and wear rate of this composite at different fibre loadings of 0.5,1,3,5 and 7 wt% were determined for the effect of acid treatment.Composites with acid treated rCF showed smaller COF (0.30–0.33) than those with untreated rCF (0.51-0.55).In contrast,wear rate was higher for the composites filled with treated rCF than those with untreated rCF.The increment of fibre loading from 5 wt% to 7 wt% decreased the wear rate for both untreated and acid treated composites owing the formation of stable patch film and transfer film.The films effectively prevented direct contact of the composites with the counterface;hence,wear was greatly inhibited.